1996
DOI: 10.1093/oxfordjournals.ndt.a027409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, predictors of disease progression and results of renal transplantation in fibrillary/immunotactoid glomerulopathy

Abstract: We contend that patients presenting with Congo-red-negative fibrillary deposits on renal biopsy should be evaluated carefully for monoclonal-gammopathy and cryoglobulins, but there is insufficient published data, as yet, to justify subclassification of FG and ITG as distinct clinical entities. Indeed, we argue that it remains to be determined if FG-ITG represents a unique condition or a forme fruste of cryoglobulin- or gammopathy-associated renal disease. Although the optimal treatment for FG-ITG has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 24 publications
2
102
1
5
Order By: Relevance
“…El tratamiento médico actual de la glomerulonefritis fibrilar e inmunotactoide en los casos en los que no se describe enfermedad sistémica subyacente o asociada, es insatisfactorio con corticoterapia e inmunosupresión (15,18). Además, se ha ensayado el trasplante renal, observándose en la mayoría de los casos recurrencia de la enfermedad, aunque el deterioro de la función renal evolucionó invariablemente más lentamente, por lo que se considera una opción atractiva en pacientes con enfermedad renal terminal (2).…”
Section: Discussionunclassified
“…El tratamiento médico actual de la glomerulonefritis fibrilar e inmunotactoide en los casos en los que no se describe enfermedad sistémica subyacente o asociada, es insatisfactorio con corticoterapia e inmunosupresión (15,18). Además, se ha ensayado el trasplante renal, observándose en la mayoría de los casos recurrencia de la enfermedad, aunque el deterioro de la función renal evolucionó invariablemente más lentamente, por lo que se considera una opción atractiva en pacientes con enfermedad renal terminal (2).…”
Section: Discussionunclassified
“…Pronovost et al (3) found that when ITG was defined on the basis of fibril size of Ͼ30 nM, 6.5% of 186 cases reviewed had ITG but that when they defined ITG on the basis of having parallel arrangement, the prevalence doubled (12%). Second, in one of the largest and most thorough reviews on the topic to date, Pronovost et al (3) found no difference in the clinical features (hypertension, hematuria, nephrotic syndrome, or renal insufficiency) at presentation when the diagnosis of ITG was subdivided on the basis of differences in fibril size (Ͼ30 versus Յ30 nM) or arrangement (random versus parallel bundles). They also recognized that any association with a lymphoproliferative disorder very much depended on the criteria used for study.…”
Section: One Entity or Two?mentioning
confidence: 99%
“…Patients with ITG range in age from 10 to 81 yr, but, on average, they have been 44 yr of age at presentation (3,4,6,7,9). More than 90% of the patients are white, and men compose from 47 to 61% of cases (3,6,11).…”
Section: Clinical and Laboratory Featuresmentioning
confidence: 99%
See 2 more Smart Citations